Cultural practices and values in the home spaces of a community that practices Adat Perpatih in Rembau, Negeri Sembilan / Mawar Masri - Masri, Mawar (2021)
The Malays have been known for their cultural richness practiced in all facets of their everyday life. However, such significant customary values and wisdoms have gradually been relinquished and will soon be forgotten due to modernisation. There are several written texts available but little had been published on home spaces in great detail. One of the traditions with intricate system is known as the Adat Perpatih, which is largely practiced by the Negeri Sembilan Malay communities. The Adat Perpatih is largely based on Islamic principles and doctrines, does not only covered the aspects of societal life which include marriage, inheritance, politics; but it also relates to other matters including architecture. Indeed, the Negeri Sembilan house is one of the most identifiable visual features which had become a significant element of identity of the Malaysian architecture. This research aims to explore the relevance of Adat Perpatih practicing society’s cultural practices of practices in modern-urban-house designs. The main objective is to establish a narrative of ritual and religious practices that are carried on during formal ceremonies or functions and the spaces that involved within authentic Negeri Sembilan house setting. Based on the evidence, it would then be possible to realign or adjust the layout and design of contemporary spaces or areas within the modern house that will closely fit into the cultural practices of the households. The study is qualitative in nature and the method employs several approaches of narrative, ethnography and case study. The review of the literature related to the origins and practices of the Negeri Sembilan community in Malaysia will provide historical narrative and context for the study. It is followed by identifying a community that knowingly maintain authentic Adat Perpatih customs during ceremonial functions for the case study. Eventually, a community that lived in Kampong Penajis in Negeri Sembilan closely matched with the purpose and was selected as the study area. The main strategy to elicit information and data collection was to record down the activities taken place during the events through participant-observation technique. Among the several key findings of research are the significance of the spaces within the house which can be considered as “sacred” and other areas as “complementary”. The findings from the study are valuable for the present and future generations in understanding the concept of the traditional space design, its functions and embedded values which is an important cultural heritage of Malaysia. Contributions to research are guideline for home design with cultural values, methods and documentations.